Staying awake – a genetic region that hinders α2 adrenergic receptor agonist‐induced sleep. (27th March 2014) - Gelegen, Cigdem; Gent, Thomas C.; Ferretti, Valentina; Zhang, Zhe; Yustos, Raquel; Lan, Fei; Yang, Qianzi; Overington, Dorothy W. U.; Vyssotski, Alexei L.; van Lith, Hein A.; Wisden, William; Franks, Nicholas P.
Abstract: How external stimuli prevent the onset of sleep has been little studied. This is usually considered to be a non‐specific type of phenomenon. However, the hypnotic drug dexmedetomidine, an agonist at α2 adrenergic receptors, has unusual properties that make it useful for investigating this question. Dexmedetomidine is considered to produce an 'arousable' sleep‐like state, so that patients or animals given dexmedetomidine become alert following modest stimulation. We hypothesized that it might be more difficult to make mice unconscious with dexmedetomidine if there was a sufficient external stimulus. Employing a motorized rotating cylinder, which provided a continuous and controlled arousal stimulus, we quantitatively measured the ability of such a stimulus to prevent dexmedetomidine loss of righting reflex in two inbred strains of mice (C57BL/6 and 129X1). We found that whereas the C57BL/6 strain required a strong stimulus to prevent dexmedetomidine‐induced hypnosis, the 129X1 strain stayed awake even with minimal stimuli. Remarkably, this could be calibrated as a simple threshold trait, i.e. a binary 'yes–no' response, which after crossing the two mouse strains behaved as a dominant‐like trait. We carried out a genome‐wide linkage analysis on the F2 progeny to determine if the ability of a stimulus to prevent dexmedetomidine hypnosis could be mapped to one or more chromosomal regions. We identified a locus on chromosome 4 with an associated Logarithm of Odds score exceeding the pre‐established threshold level. These results show that complex traits, such as the ability of a stimulus to reverse drug‐induced hypnosis, may have precise genetic determinants. Abstract : This paper shows that two in‐bred strains of mouse, C57BL/6 and 129X1 respond very differently to an external stimulus when given the hypnotic drug dexmedetomidine, an agonist at α2 adrenergic receptors. Both strains respond identically in the absence of a stimulus, however, the C57BL/6 strain required a strong stimulus to prevent dexmedetomidine‐induced hypnosis whereas the 129X1 strain stayed awake even with minimal stimuli. A genome‐wide linkage analysis identified a key determinant on chromosome 4 which behaved as a dominant‐like trait.